TESTING THE EFFICIENCY OF GLOBAL CRUDE OIL MARKETS IN THE WEAK FORM UNDER THE UNIT ROOT MODEL - Haider Nasser Hussein Al Mayali; Maithem R. Hadi (Scholars Digest Publishing, 2025)
The importance of this study is gained from the importance of its subject through the methods of one of the most important topics in economics and finance, which is the topic of fluctuations in crude oil markets. In addition, the global oil industry occupies great importance, especially at the present time, as the crude oil commodity is described as the most important global commodity among All other goods are also described as the most important good, Because of its great importance, it is subject to various fluctuations. This is due to its influence on the political, economic and social events that occur in different countries. Certainly, due to the various fluctuations witnessed by the crude oil commodity, it has become vulnerable to mispricing and control by speculators and global policy makers. From this standpoint, the importance of the study emerged. In an attempt to discover the structure, nature and how to manage the crude oil market, It is no secret to anyone that studying the nature of fluctuations in crude oil markets has become a permanent goal for researchers in recent times, especially after the Covid-19 crisis and the decline it caused in global crude oil prices that had never been witnessed before, as the price of crude oil reached below $20 per barrel. Perhaps the most important question being investigated is whether the global crude oil markets fluctuate randomly or is there someone controlling the market? The study aims to test the efficiency of the market in a weak manner and within the framework of single root tests, including the modified Dickey and Fuller test. The sample of the current study included (53) crude oil materials distributed in (12) countries around the world, it is the first research in the world to test (53) different types of global oil crudes. The study concluded that the markets for crude oils and the oil crudes sampled in the research are weakly inefficient and do not follow a random walk within the framework of the Dickey-Fuller model.